Strategi pengendalian risiko dalam produk pembiayaan syariah: Studi kasus murabahah, ijarah, dan mudharabah - nurmala, enjelita septi (Maliki Interdisciplinary Journal, 2025)
The Islamic finance industry in Indonesia has experienced rapid growth in recent years, driven by increasing public awareness of Islamic economic principles. Financing products such as Murabahah, Ijarah, and Mudharabah serve as primary instruments in supporting Sharia-based economic activities. However, each of these products carries distinct characteristics and risk profiles, requiring tailored risk control strategies that align with both Sharia principles and prevailing regulations. This study aims to analyze the main types of risk associated with each contract and the mitigation strategies implemented to address them. The research uses a literature review method combined with a descriptive analysis of recent empirical findings. The results indicate that Murabahah carries a high credit risk, Ijarah is exposed to operational and legal risks, while Mudharabah is vulnerable to information asymmetry and moral hazard. Risk mitigation strategies include the application of prudential banking principles, the 5C approach, asset monitoring, insurance coverage, business mentoring, and digitalization of risk management systems. Furthermore, integrating Sharia principles with global risk management standards is considered crucial for strengthening the resilience of the Islamic finance sector. This study is expected to contribute to the development of a comprehensive and Sharia-compliant risk management system within Islamic financial institutions.